2021
DOI: 10.1186/s12879-021-06834-w
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and multidrug resistance of Campylobacter spp. at duck farms and associated environmental and anthropogenic risk factors in Bangladesh

Abstract: Background The alarming rise in multi-drug resistant (MDR) zoonotic pathogens, including Campylobacter spp., has been threatening the health sector globally. In Bangladesh, despite rapid growth in poultry sector little is known about the potential risks of zoonotic pathogens in homestead duck flocks. The aim of this study was to understand the occurrence, species diversity, and multi-drug resistance in Campylobacter spp., and identify the associated risk factors in duck farms in Bangladesh. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…There is no consensus on which of the two Campylobacter species, C. coli and C. jejuni, is dominant in poultry and livestock. In agreement with our findings, recent studies from Africa, Asia, and Europe have reported significantly more C. coli in chicken (Torralbo et al, 2015;Wieczorek et al, 2020), ducks (Uddin et al, 2021), poultry meat (Dekker et al, 2019), and pigs (Padungtod and Kaneene, 2005;Wieczorek et al, 2021). On the contrary, several studies have found almost exclusively C. jejuni in chicken (Guyard-Nicodème et al, 2015;Karikari et al, 2016), poultry meat (Szosland-Fałtyn et al, 2018), quails (Cox et al, 2018), and wild birds (Hald et al, 2015).…”
Section: Adjusted Ratio Pr (95% Ci)supporting
confidence: 92%
“…There is no consensus on which of the two Campylobacter species, C. coli and C. jejuni, is dominant in poultry and livestock. In agreement with our findings, recent studies from Africa, Asia, and Europe have reported significantly more C. coli in chicken (Torralbo et al, 2015;Wieczorek et al, 2020), ducks (Uddin et al, 2021), poultry meat (Dekker et al, 2019), and pigs (Padungtod and Kaneene, 2005;Wieczorek et al, 2021). On the contrary, several studies have found almost exclusively C. jejuni in chicken (Guyard-Nicodème et al, 2015;Karikari et al, 2016), poultry meat (Szosland-Fałtyn et al, 2018), quails (Cox et al, 2018), and wild birds (Hald et al, 2015).…”
Section: Adjusted Ratio Pr (95% Ci)supporting
confidence: 92%
“…The improper antimicrobial drug used for humans is diffusive in developing countries and is a significant contributor to growing the public health threat of AMR-resistant bacteria (Roess et al, 2013). In recent years, the indiscriminate use of antibiotics in animals and poultry is thought to be an important factor to develop of AMR Al-Salauddin et al, 2015;Sohidullah et al, 2016;Rahman et al, 2016;Talukder and Ahmed, 2016;Roy et al, 2017;Jahan et al, 2017;Kabir et al, 2018a;Kabir et al, 2018b;Kamal et al, 2018;Alam et al, 2019;Rumi et al, 2019;Saif et al, 2019;Masud et al, 2020;Alam et al, 2020;Sarker et al, 2020;Mridha et al, 2020;Matubber et al, 2021;Uddin et al, 2021;Tresha et al, 2021;Eashmen et al, 2021;Haque et al, 2021;Hosain et al, 2021;Arif et al, 2022;Hoque et al, 2022). In Bangladesh, the most common reason for choosing an antimicrobial is personal experience and perception (68%), rather than the cultural sensitivity test which may be due to a lack of vet diagnostic facilities and the unwillingness of the veterinary personnel (Pokharel et al, 2020).…”
Section: Development Of Antimicrobial Resistance (Amr)mentioning
confidence: 99%
“…Campylobacters are widely distributed as a normal flora in the gut of both domestic and wild animals, and are also found in environmental samples, including surface water, soil, and feeds [ 1 ]. The incidence of campylobacters in environmental sources is mainly related to fecal contamination.…”
Section: Introductionmentioning
confidence: 99%